157k views
4 votes
-13(v-6)=-5v+2(5v+12)

User V K
by
5.5k points

1 Answer

4 votes

Answer:

v = 3

Explanation:


-13(v-6)=-5v+2(5v+12)\qquad\text{use the distributive property}\\\\(-13)(v)+(-13)(-6)=-5v+(2)(5v)+(2)(12)\\\\-13v+78=-5v+10v+24\qquad\text{cobine like terms}\\\\-13v+78=(-5v+10v)+24\\\\-13v+78=5v+24\qquad\text{subtract 78 from both sides}\\\\-13v+78-78=5v+24-78\\\\-13v=5v-54\qquad\text{subtract}\ 5v\ \text{From both sides}\\\\-13v-5v=5v-5v-54\\\\-18v=-54\qquad\text{divide both sides by (-18)}\\\\(-18v)/(-18)=(-54)/(-18)\\\\v=3

User Roscoe
by
5.2k points